KAJIAN PENGERING GABAH DENGAN WADAH PENGERING BERBENTUK SILINDER DANMEKANISME PENGADUK PUTAR - Nusyirwan (Department of Mechanical Engineering Atma Jaya Catholic University of Indonesia, 2014)
Rice yield in this market are still drained manually by using the power of the Sun and drying process is done in a long time. Moisture content of the product is not uniform, and the resulting dried grain capacity is limited, because it requires a big place in the drying process. Rice dryers available on the market have not been manufactured with quality drying is not good because of the uneven results of drying and drying inefficient. With the above background, the dryer can be designed to work in continuous material and product is can occur at any time. Equipment dryers are equipped with commutator so that drying can take place constantly. Testing is done is to take a sample of every 1 kg of rice and measured levels of moisture content. Drying characteristics of optimization testing is to control the speed of the stirrer shaft, and evaluate the results of testing the uniformity of drying is to divide the result of drying to 8 mass fraction is then weighed their respective weight. Tests using rice dryer drum drying with a stirring mechanism, it can be concluded that the decrease in moisture content and degree of drying and drying time is affected by the speed of rotation of the agitator shaft is linear. Testing is done by varying the agitator rotation rpm 30, 35 and 40 rpm rpm. On lap 40 rpm going very fast drying results in the material to be cracked. In this study, drying time is used for drying rice as much as 8 kg with a level of 24% to 14% is 30 minutes with stirring speed 35 rpm,and the uniformity of drying results 86.6%.